2018
DOI: 10.1016/j.jaci.2017.05.036
|View full text |Cite
|
Sign up to set email alerts
|

A distinct biomolecular profile identifies monoclonal mast cell disorders in patients with idiopathic anaphylaxis

Abstract: Patients with clonal mast cell disease can present as having IA. Distinct clinical and laboratory features can be used to select those patients more likely to have an underlying clonal mast cell disorder (monoclonal mast cell activation syndrome or systemic mastocytosis) and thus candidates for a bone marrow biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…These patients also had relatively low serum tryptase levels (all <20 ng/ml) at the time when the PB ASqPCR assay was negative. We have reported a similar observation in adult patients with idiopathic anaphylaxis with isolated bone marrow mastocytosis (Carter et al, 2015(Carter et al, , 2018, which is supported by other reports (Erben et al, 2014;Kristensen et al, 2014Kristensen et al, , 2017Carter et al, 2018). This is consistent with the low frequency of cells bearing the mutated allele in patients with minimal disease or improving clinical status.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These patients also had relatively low serum tryptase levels (all <20 ng/ml) at the time when the PB ASqPCR assay was negative. We have reported a similar observation in adult patients with idiopathic anaphylaxis with isolated bone marrow mastocytosis (Carter et al, 2015(Carter et al, , 2018, which is supported by other reports (Erben et al, 2014;Kristensen et al, 2014Kristensen et al, , 2017Carter et al, 2018). This is consistent with the low frequency of cells bearing the mutated allele in patients with minimal disease or improving clinical status.…”
Section: Discussionsupporting
confidence: 91%
“…There are several published algorithms to assist in the diagnostic approach and determine which adults are more likely to have systemic disease (Alvarez-Twose et al, 2010;Gulen et al, 2014;Carter et al, 2018). Recent studies identifying and quantitating the KIT D816V mutation in peripheral blood (PB) in adults have suggested it to be a valuable tool for diagnosis, (Kristensen et al, 2011(Kristensen et al, , 2014Jara-Acevedo et al, 2015) to determine disease burden and monitoring (Erben et al, 2014), and to assess response to therapy (Hoermann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Carter and colleagues investigated 56 subjects who had more than one episodes of unexplained anaphylaxis with BM examination and found evidence of MC clonal disease in 14% of cases. The authors proposed the “NIH Idiopathic Clonal Anaphylaxis Score” (NICAS) tool which uses four parameters: gender, clinical symptoms, baseline serum tryptase level (“cut‐off” at 11.4 ng/mL) and allele‐specific PCR testing to detect the presence or absence of KIT D816V in peripheral blood.…”
Section: Mast Cell Disorders Misdiagnosed As Idiopathic Anaphylaxismentioning
confidence: 99%
“…10,11 Mastocytosis is an important risk factor for IA, and in patients with IA a clonal mast cell disease should be considered in the differential diagnosis. 12,13 Mast cells, along with basophils, are the effector cells in human anaphylaxis, and the symptoms are caused by release of vasoactive mediators and cytokines from activated mast cells and basophils. Idiopathic anaphylaxis is therefore classified under idiopathic mast cell activation syndromes in a recent classification of mast cell disorders.…”
Section: Introductionmentioning
confidence: 99%
“…25 However, in a prospective study of patients with IA, ex vivo studies of cultured mast cells indicated no evidence of a hyperreponsive mast cell phenotype. 12 Another theory of IA pathogenesis involves activated lymphocytes. Patient with IA have been shown to have a higher percentage of activated T-cells (CD3þ HLA-DRþ) in peripheral blood during acute episodes compared with patients in remission.…”
Section: Introductionmentioning
confidence: 99%